Preventive Nutrition The Comprehensive Guide for Health Professionals - Bendich, Adrianne; Deckelbaum, Richard J.; SpringerLink (Online service) (Totowa, NJ : Humana Press, 2010)
Evidence-based nutritional interventions are now a critical component of preventive medicine, employed in a wide variety of medical scenarios. Preventive Nutrition: A Comprehensive Guide for Health Professionals, Fourth Edition gives health professionals up-to-date, comprehensive reviews that evaluate the dietary practices and interventions that have been shown to reduce disease risk and improve health outcomes. This is the flagship volume for the book series, Nutrition and Health, which has become an essential tool for health professionals. As the state of global health and nutrition have changed much since the publication of the Third Edition, this major revised and expanded Fourth Edition includes newly authored chapters and features analysis of the results of the Women s Health Initiative, the largest intervention study ever undertaken and completed in postmenopausal women. Other new material includes chapters reviewing the evidence concerning econutrition, micronutrients and major cancers, and cognitive function and other mental health areas. Also discussed are the importance of gastric acid secretions, the nutritional effects of current therapies, and the latest information on the biology of obesity and its relationship to Type 2 diabetes. One key new feature of this edition is a chapter on behavioral strategies to help assure compliance with dietary regimes, maximizing the health benefits of preventive nutrition. The authors have created the most comprehensive and up-to-date review of the nutritional strategies available for the prevention of disease and the promotion of health through nutrition. Patients are looking for credible information from their health care providers about a whole range of subjects covered here, including ß-carotene, lycopene, antioxidants, folate, and the myriad of bioactive phytochemicals found in garlic and other foods. With sections on cardiovascular disease, diabetes, and pregnancy among many others, this volume will be of great value to practicing health professionals, including physicians, nutritionists, dentists, pharmacists, dieticians, health educators, policy makers, health economists, regulatory agencies and research investigators. An entire section covers nutrition transitions around the world including Eastern Europe, Latin America and Asia as well as goals for preventive nutrition in developing countries.
Global Issues -- Public Health Benefits of Preventive Nutrition -- Health Economics of Preventive Nutrition -- Econutrition: Preventing Malnutrition with Agrodiversity Interventions -- Nutrition in the Age of Polypharmacy -- Cancer Prevention -- Diet and Childhood Cancer: Preliminary Evidence -- Prevention of Upper Gastrointestinal Tract Cancers -- Factors in the Causation of Female Cancers and Prevention -- The Role of Nutrition and Diet in Prostate Cancer -- Dietary Supplements and Cancer Risk: Epidemiologic Research and Recommendations -- Cardiovascular Disease Prevention -- N-3 Fatty Acids from Fish and Plants: Primary and Secondary Prevention of Cardiovascular Disease -- Cardiovascular Effects of Trans Fatty Acids -- Antioxidant and B-vitamins and Atherosclerosis -- B Vitamins in the Prevention of Cognitive Decline and Vascular Dementia -- Diabetes and Obesity -- The Women's Health Initiative: Lessons for Preventive Nutrition -- Role of Nutrition in the Pathophysiology, Prevention, and Treatment of Type 2 Diabetes and the Spectrum of Cardiometabolic Disease -- Nutrition, Metabolic Syndrome, and Diabetes in the Senior Years -- Adipokines, Nutrition, and Obesity -- Diet, Obesity, and Lipids: Cultural and Political Barriers to Their Control in Developing Economies -- Prevention of Major Disabilities; Improvement in Health Outcomes -- Diet, Osteoporosis, and Fracture Prevention: The Totality of the Evidence -- Gastric Acid Secretions, Treatments, and Nutritional Consequences -- Nutritional Antioxidants, Dietary Carbohydrate, and Age-Related Maculopathy and Cataract -- Micronutrients and Immunity in Older People -- Micronutrients: Immunological and Infection Effects on Nutritional Status and Impact on Health in Developing Countries -- HIV and Nutrition -- Optimal Pregnancy/Infancy Outcomes -- Folic Acid/Folic Acid-Containing Multivitamins and Primary Prevention of Birth Defects and Preterm Birth -- Maternal Nutrition and Preterm Delivery -- Linking Prenatal Nutrition to Adult Mental Health -- Nutrition Transitions Around the World -- Nutritional Habits and Obesity in Latin America: An Analysis of the Region -- Effects of Western Diet on Risk Factors of Chronic Disease in Asia -- Goals for Preventive Nutrition in Developing Countries -- Preventive Nutrition and the Food Industry: Perspectives on History, Present, and Future Directions -- The Role of Preventive Nutrition in Clinical Practice.
Keywords: Medicine; Nutrition; Family medicine; Geriatrics; Internal medicine; Personal health and hygiene; Emergency medicine; Medicine & Public Health; Clinical Nutrition; Nutrition; Internal Medicine; Primary Care Medicine; General Practice / Family Medicine; Geriatrics/Gerontology.